2018
DOI: 10.1002/jmv.25228
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of uncommon HIV‐1 non‐B subtypes and circulating recombinant forms and trends in transmission of antiretroviral drug resistance in patients with primary infection during the 2013‐2015 period in Marseille, Southeastern France

Abstract: Primary HIV-1 infections (PHI) with non-B subtypes are increasing in developed countries while transmission of HIV-1 harboring antiretroviral resistance-associated mutations (RAMs) remains a concern. This study assessed non-B HIV-1 subtypes and RAMs prevalence among patients with PHI in university hospitals of Marseille, Southeastern France, in 2005-2015 (11 years). HIV-1 sequences were obtained by in-house protocols from 115 patients with PHI, including 38 for the 2013-2015 period. On the basis of the phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The prevalence of RPV-resistant isolates ranges from 4 to 10% in individuals who are treatment naive (26)(27)(28)(29)(30)(31)(32)(33) to 42 to 72% in individuals with viremia during non-RPVcontaining ART (34)(35)(36)(37)(38)(39)(40)(41). Three clinical studies evaluated the efficacy of RPV-containing regimens compared to EFV-containing regimens in treatment-naive individuals (the ECHO, THRIVE, and STaR trials), all of which identified multiple RPV-associated resistance mutations that arose in subjects on RPV-containing ART (42,43).…”
mentioning
confidence: 99%
“…The prevalence of RPV-resistant isolates ranges from 4 to 10% in individuals who are treatment naive (26)(27)(28)(29)(30)(31)(32)(33) to 42 to 72% in individuals with viremia during non-RPVcontaining ART (34)(35)(36)(37)(38)(39)(40)(41). Three clinical studies evaluated the efficacy of RPV-containing regimens compared to EFV-containing regimens in treatment-naive individuals (the ECHO, THRIVE, and STaR trials), all of which identified multiple RPV-associated resistance mutations that arose in subjects on RPV-containing ART (42,43).…”
mentioning
confidence: 99%
“…These genotypic changes do not confer consistently decreased susceptibility by themselves when viral strains are subjected to phenotypic testing [ 33 , 34 ]. Furthermore, studies of resistance pattern that emerge in patients receiving ART indicate that presence of polymorphisms before start of ART may provide a background facilitating emergence of specific selection pathways to secondary resistance[ 27 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 subtype B is the most common subtype in developed countries, and accounts for approximately 11%–12% of the global epidemic [ 4 ]. Primary HIV-1 infections with various non-B subtypes (hereafter called non-B) are increasing in developed countries [ [4] , [5] , [6] ]. There have been reports on the difference in disease progression among the patients infected with non-B [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%